Identification and Functional Characterization of Peptides With Antimicrobial Activity From the Syphilis Spirochete, Treponema pallidum - Houston, Simon; Schovanek, Ethan; Conway, Kate M. E.; Mustafa, Sarah; Gomez, Alloysius; Ramaswamy, Raghavendran; Haimour, Ayman; Boulanger, Martin J.; Reynolds, Lisa A.; Cameron, Caroline E. (Frontiers in Microbiology, 2022)
The etiological agent of syphilis, Treponema pallidum ssp. pallidum, is a highly invasive “stealth” pathogen that can evade the host immune response and persist within the host for decades. This obligate human pathogen is adept at establishing infection and surviving at sites within the host that have a multitude of competing microbes, sometimes including pathogens. One survival strategy employed by bacteria found at polymicrobial sites is elimination of competing microorganisms by production of antimicrobial peptides (AMPs). Antimicrobial peptides are low molecular weight proteins (miniproteins) that function directly via inhibition and killing of microbes and/or indirectly via modulation of the host immune response, which can facilitate immune evasion. In the current study, we used bioinformatics to show that approximately 7% of the T. pallidum proteome is comprised of miniproteins of 150 amino acids or less with unknown functions. To investigate the possibility that AMP production is an unrecognized defense strategy used by T. pallidum during infection, we developed a bioinformatics pipeline to analyze the complement of T. pallidum miniproteins of unknown function for the identification of potential AMPs. This analysis identified 45 T. pallidum AMP candidates; of these, Tp0451a and Tp0749 were subjected to further bioinformatic analyses to identify AMP critical core regions (AMPCCRs). Four potential AMPCCRs from the two predicted AMPs were identified and peptides corresponding to these AMPCCRs were experimentally confirmed to exhibit bacteriostatic and bactericidal activity against a panel of biologically relevant Gram-positive and Gram-negative bacteria. Immunomodulation assays performed under inflammatory conditions demonstrated that one of the AMPCCRs was also capable of differentially regulating expression of two pro-inflammatory chemokines (monocyte chemoattractant protein-1 [MCP-1] and interleukin-8 [IL-8]). These findings demonstrate proof-of-concept for our developed AMP identification pipeline and are consistent with the novel concept that T. pallidum expresses AMPs to defend against competing microbes and modulate the host immune response.